Upaya Penting Dalam Menanggulangi TB Dengan Strategi Yang Paling Efektif Untuk Memastikan Kepatuhan Terhadap Terapi Dengan Pengawasan - Wahyuni, Tri; Idris, Idris; Ardianto, Ardianto; Fahamsya, Arifina; Cahyanta, Agung Nur; Wicaksono, Rizky Rahadian (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Tuberculosis is a health problem, both in terms of mortality rates, morbidity rates, and diagnosis and therapy. The purpose of Community Service is to increase knowledge about the prevention and treatment of Tuberculosis and its management in the community. The method of implementing community service uses health education on tuberculosis prevention, assistance and assessment of the level of understanding of tuberculosis and prevention of tuberculosis. The results of the Community Service activities obtained that there was an increase in the knowledge and skills of community participants about tuberculosis. The conclusion is that Community Empowerment with TB Cadres has an important role, especially in efforts to find, provide information and accompany TB patients.